Comprehensive Comparative Genomic and Transcriptomic Analyses of the Legume Genes Controlling the Nodulation Process - Qiao, Zhenzhen; Pingault, Lise; Nourbakhsh-Rey, Mehrnoush; Libault, Marc (Frontiers in Plant Science, 2016)
Nitrogen is one of the most essential plant nutrients and one of the major factors  limiting crop productivity. Having the goal to perform a more sustainable agriculture, there  is a need to maximize biological nitrogen fixation, a feature of legumes. To enhance our understanding of the molecular mechanisms controlling the interaction between legumes  and rhizobia, the symbiotic partner fixing and assimilating the atmospheric nitrogen for the  plant, researchers took advantage of genetic and genomic resources developed across  different legume models (e.g. Medicago truncatula, Lotus japonicus, Glycine max and  Phaseolous vulgaris) to identify key regulatory genes of the nodulation process. In this  study, we are presenting the results of a comprehensive comparative genomic analysis to  highlight orthologous and paralogous relationships between the legume genes controlling nodulation. Mining large transcriptomic datasets, we also identified several orthologous  and paralogous genes characterized by the induction of their expression during nodulation  across legume plant species. This comprehensive study prompts new insights into the  evolution of the nodulation process in legume plant and will benefit the scientific  community interested in the transfer of functional genomic information between species.